The Integration of Foreign Students in the Portuguese School of the 1st Cycle of Basic Education: the Case of a School Grouping in the Municipality of Viseu - Nunes, Catarina (2016)
The present study aims to understand whether the foreign students who have different nationalities but the Portuguese are integrated into the school of the 1st Cycle of Basic Education. With this purpose, a descriptive and phenomenological research was conducted, making use of documental analysis, as well as semi-structured interviews and sociometric tests. These two data collecting tools were applied to students attending from the 1st to the 4th school years, in three 1st Cycle of Basic Education schools, within a school grouping in Viseu. The data obtained through the interviews allow us to conclude that foreign students, in general, feel integrated both in the school and in the class they belong to. However, the analysis of the results of the sociometric tests reveals other data, allowing us to conclude that one of the students is neither integrated in the school, nor in the class he is part of.